'Pure' partial trisomy 2q in a male owing to malsegregation of a maternal translocation t(X;2)(p22.3;q32.1). Issue 1 (February 1985) - Plessis, G; Couturier, J; Turleau, C; Despoisses, S; Delavenne, J
Abstract : This report describes a male infant with partial trisomy 2q: 46, Y, der(X), t(X;2) (p22.3;q32.1)mat. The phenotype was compatible with partial trisomy 2q syndrome. Replication studies showed a random X inactivation in the mother. Soluble isocitrate dehydrogenase (IDH-1) dosage was within the expected range for a trisomic patient and favours the assignment of this locus to the region 2q32—-qter.